Studies on precast reinforced concrete floor panels using oil palm shell aggregate - Ng, Chee Hiong (2010)
Experimental studies were performed on precast reinforced concrete floor panels using lightweight concrete. The mix design of lightweight concrete was developed using 70% Oil Palm Shell (OPS) and 30% granite as coarse aggregates. Its basic engineering properties using standard specimens were studied under water and steam curing conditions. A total of 50 prototype precast floor panels of solid section, semi-precast and C-channels were made. At initial stage, they were investigated using 3 m spans only. C-channel having smaller cross-section and reduced self-weight showed the best structural performance. Further extensive investigations were made using C-channels of 3, 4, 5, 6, 7 and 8 m spans. Two-line loads and uniform distributed load were applied for tests at ultimate failure and serviceability conditions. The flexural properties determined were (i) service load and moment capacity, (ii) deflection, (iii) crack width, (iv) ductility, (v) strains in concrete and steel, and (vi) end rotation. The deflection recovery and the flange load capacity of C-channels were studied. The lifting hooks, bearing width and the monolithic behaviour at panel joints using pull-down mechanism were also investigated. The experimental investigations were verified with British Standards (BS 8110), Eurocode (EC2), American Standard (ACI 318) and Indian Standard (IS). The experimental results obtained for C-channel have fulfilled the requirements as stipulated in the above standards. The study has provided the critical understanding on the behaviour of C-channel, thereby confirming that C-channel being fully precast reinforced concrete panel is structurally more efficient, promising and viable alternative to the conventional floor system.